PENINGKATAN KEMAMPUAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN MELALUI PENDAMPINGAN BERBASIS BIMBINGAN INDIVIDU DI SDN 13 SUNGAI PINANG - Syafrizal, Syafrizal (Jurnal Manajemen Pendidikan, 2018)
The results of observations and supervision carried out by the authors indicate that teachers at SDN 13 Sungai Pinang do not have the ability and good skills in carrying out their duties, especially in terms of using learning media. The purpose of this study was to describe and obtain information about efforts to improve the ability of teachers to use learning media by conducting individual guidance-based mentoring at SDN 13 Sungai Pinang. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 3 class teachers at SDN 13 Sungai Pinang. Research data was collected using observation sheets. Data were analyzed using average. The results showed that individual guidance-based mentoring activities can improve the ability of teachers to design, determine and use learning media. This is evidenced by the initial data of the teacher's ability before the implementation of individual guidance-based mentoring activities is still in the unfavorable category. Then after conducting individual guidance-based mentoring activities, the teacher's ability increases which can be seen from the improvement of the quality of learning media created by the teacher and an increase in the teacher's ability to use the media in the class to be 79.67 (good) in cycle I and after that increase in cycle II to be 87.33 (very good).